Undrained Shear Strength of Peat Soil Improved with Pond Ash-Hydrated Lime Admixture - Md. Yusof, Zeety; Ain Mohd Akhir Johari, Nurul; Mohamed, Kamaruzzaman; Bagus Mohamed Jais, Ismacahyadi; ., . (International Journal of Engineering and Technology, 2019)
The low shear strength and high moisture content can be highly related to peat soil.Â It can be categorized as a baffling soil because of its high humidity in the peat soil particle. The reasons for why settlements need to occur after heavy load has been applied to the peaty soil need to be discovered.Â Therefore, in this study, the objective of work is linked to the strength of the untreated and treated peat soil with in an effective way but with a low budget.Â The strength of the untreated natural peat and treated peat soil with pond ash-hydrated lime which are reacting as a binder in the peat soil treated particles was designed.Â The different strength of soaking time (0, 7, 14 and 21 days) of the samples is compared to know the different strength of different soaking time by using Unconsolidated Undrained (UU) test.Â The results show that the shear strength was increased when the pond ash-hydrated lime was added to the soil.Â Â